Laparoscopic Management of an Abdominal Pregnancy - Aarthi Srinivasan; Suzanne Millican (Case Reports in Obstetrics and Gynecology)
Background. Ectopic pregnancy is one of the leading causes of significant maternal morbidity and mortality. Abdominal surgeries increase the risk of postoperative adhesions. We here present a case of omental ectopic pregnancy in a patient with a prior history of cesarean section. Case. A 20-year-old female presented with a two-day history of crampy lower abdominal pain. Patient was hemodynamically stable with a beta HCG of 1057 mI/mL. Transvaginal ultrasound did not show an intrauterine pregnancy but revealed an ill-defined mass in the midline pelvis extending to the right of the midline. Diagnostic laparoscopy revealed large clots in the pelvis with normal uterus and adnexa. Intra-abdominal survey revealed an omental adhesion close to the right adnexa with a hematoma. Partial omentectomy was completed and the portion of the omentum with the hematoma was sent to pathology for confirmation. Final pathology confirmed the presence of chorionic villi consistent with products of conception. Conclusion. Omental ectopic pregnancy is a rare diagnosis and often missed. We recommend careful intra-abdominal survey for an ectopic pregnancy in the presence of hemoperitoneum with normal uterus and adnexa. This can be safely achieved using laparoscopy in early gestational ages when the patient is hemodynamically stable.